Prevalence, risks factors, and control of hypertension in Guinean older adults in 2021: a cross-sectional survey - Alioune Camara; Alpha Koné; Thierno Mamadou Millimono; Abdoulaye Sow; Amadou Kaké; Pierre-Marie Preux; Mamadou Dadhi Balde; Pierre Jesus (BMC, 2024)
Abstract Background The incidence of arterial hypertension increases with the aging of the population, but its magnitude remains insufficiently assessed. The aim of this study was to investigate the prevalence of hypertension and associated factors in elderly people in Guinea. Methods Data were obtained from a cross-sectional general population survey, conducted among people aged ≥ 60 years. A stratified enumeration area random sample survey was conducted in the four natural regions of Guinea from February to April 2021. This study included an interview on sociodemographic data, and a clinical examination. Hypertension was defined as systolic blood pressure ≥ 140mmHg and/or diastolic blood pressure ≥ 90mmHg or previous diagnosis of hypertension (with or without antihypertensive medication). Hypertension control was defined as blood pressure below 140/90 mmHg during treatment. Age-standardized prevalence was calculated, and logistic regression was used to examine factors associated with hypertension. Results A total of 1698 adults (1079 men, mean age: 71.6 ± 9.4 years) had at least two blood pressure measurements. The standardized prevalence of hypertension was 61.4% [95% CI: 61.3-61.6], ranging from 52% in Middle Guinea to 67% in Upper Guinea, and was higher in women (65.2%: 65.0-65.4) than in men (59.1%:58.9-59.3). Among those with hypertension, 46.7% were unaware of their condition before the survey and 49.6% were on treatment and only 18.5% had controlled hypertension. Whatever the residence (rural or urban), increasing age, being unmarried, working as a trader or functionary, jobless, living in upper Guinea, low monthly income, intake of extra salt, known diabetic, overweight, and obesity increased the risk of hypertension. In urban area, female sex (AOR: 1.14: 1.12-1.17), living in lower Guinea (AOR: 3.08: 2.97-3.20), being Maninka (AOR: 1.26: 1.21-1.31), being Nguerze (AOR: 1.71: 1.63-1.81) increased the risk of hypertension, but living in forest Guinea (AOR: 0.88: 0.83-0.93), being Soussou (AOR: 0.88: 0.85-0.92) decreased the risk. In rural area, living in forest Guinea (AOR: 2.14: 2.03-2.26), being Soussou (AOR: 1.14: 1.12-1.17) increased the risk of hypertension, but female sex (AOR: 0.96: 0.94-0.98), living in lower Guinea (AOR: 0.87: 0.85-0.89), being Maninka (AOR: 0.94: 0.92-0.97), being Nguerze (AOR: 0.50: 0.47-0.52) decreased the risk. Conclusion Hypertension is a major problem in the elderly population in Guinea, and the level of treatment and control in elderly with known hypertension is inadequate. The place of hypertension among cardiovascular diseases and the identification of associated factors underlines the need to develop innovative approaches to control this major risk factor.